Pharmacokinetics of gentamicin after intratracheal administration in tracheotomy patients - Gu Chao-Ning; Shan Hong-Wei; Deng Yu-Ling; Zhu Chai-Juan; Ding Xue-Hua; Gu Qiu-Ping (Acta Pharmacologica Sinica, 2016)
Seventeen tracheotomy patients were given gentamicin (Gen) into trachea at the dosage of 2 and 4 mg.kg-1. Gen concentration in serum was determined by fluorescence polarization immunoassay. Pharmacokinetic parameters were calculated by micro-computer pharmacokinetic program (MCPKP). T1/2Ka, Tp, and Cmax were 0.6 +/- 0.3 h, 1.7 +/- 0.7 h, and 4.6 +/- 1.8 micrograms.ml-1, respectively in 4 mg.kg-1 group and 0.3 +/- 0.3 h, 0.9 +/- 0.5 h, and 0.4 +/- 0.2 microgram.ml-1, respectively in 2 mg.kg-1 group (P < 0.05). T1/2Kel was 30 +/- 11 h in patients of serum creatine (Cr) > 2 mg% and 6 +/- 5 h in patients of Cr < 2 mg% (P < 0.01). No significant difference could be found between Cmax of different renal function patients (P > 0.05).